KEABSAHAN AKAD JUAL BELI MULTI LEVEL MARKETING DALAM PERSPEKTIF TEORI HUKUM PERJANJIAN SYARIâ€˜AH (NAZHÃ‚RIYYAT AL-â€˜UQÃ›D): The Validity of Multi-Level Marketing Contracts from the Perspective of Naẓariyyat al-‘Uqūd - Mirza, Iskandar (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2016)
According to the form of legal development (al-tasyrî‘), nazhâriyyat al-‘uqûd is resulted from the transformation process of sources, principles, and bases of Islamic economic values which are derived from the Quran and the Sunna into the pracstical of Islamic business. It is also firstly begun through the analysis and translation on nazhâriyyat al-‘uqûd by the muslim scholars in the book of fiqh. The concept of business transaction (mafhum al-‘uqûd) in Islamic legal contract is based on three theories: First, the theory of property rights (nazhâriyyat al-milkiyyah ‘alâ al-mâl); Second, the theory of business transaction (nazhâriyyat al-‘uqûd); and Third, the theory of property management (nazhâriyyat al-intiqal al-milkiyyah). These are starting point to examine the consept of business transaction (mafhum al-‘uqûd) within Islamic legal contract to dealth with the Islamic practical rule of direct selling.